Hydrophilic-coated catheter appreciation study in a pediatric population - Boucher, Andréanne; Cloutier, Jonathan; Lebel, Sylvie; Hamel, Micheline; Lamontagne, Pascale; Bolduc, Stéphane (Canadian Urological Association Journal, 2013)